Peptides from the Mycobacterium tuberculosis Rv1980c protein involved in human cell infection: Insights into new synthetic subunit vaccine candidates (2010)
Mycobacterium tuberculosis infection continues to be a major cause of morbidity and mortality throughout the world. The vast complexity of the intracellular pathogen M. tuberculosis and the diverse mechanisms by which it can invade host cells highlight the importance of developing a fully protective vaccine. Our vaccine development strategy consists of including fragments from multiple mycobacterial proteins involved in cell invasion. The aim of this study was to identify high activity binding peptides (HABPs) in the immunogenic protein Rv1980c from M. tuberculosis H37Rv with the ability to inhibit mycobacterial invasion into U937 monocyte-derived macrophages and A549 cells. The presence and transcription of the Rv1980c gene was assessed in members belonging to the M. tuberculosis complex and other nontuberculous mycobacteria by PCR and RT-PCR, respectively. Cell surface localization was confirmed by immunoelectron microscopy. Three peptides binding with high activity to U937 cells and one to A549 cells were identified. HABPs 31100, 31101, and 31107 inhibited invasion of M. tuberculosis into A549 and U937 cells and therefore could be promising candidates for the design of a subunit-based antituberculous vaccine. © 2010 by Walter de Gruyter Berlin New York.